Evaluation of Social Media Strategies in PR Practice by Tertiary Institutions in Nigeria - George Nathan Brown; Ifeanyi Martins Nwokeocha; Esther George Ntegwung (Syntax Corporation Indonesia, 2025)
Social media has altered the fabric of public relations practice, redefining how institutions communicate, build trust, and sustain reputation. Nigerian tertiary institutions, though historically reliant on conventional channels, are increasingly compelled to adopt digital platforms to engage stakeholders who now demand immediacy, accessibility, and participation. This study examined the social media strategies employed by selected tertiary institutions in Akwa Ibom State, with particular focus on their effectiveness in public relations practice. The study was hinged on the Uses and Gratifications Theory and the Situational Theory of Publics. The research employed a mixed-methods design, combining survey data from 165 public relations professionals, social media managers, and communication officers with semi-structured interviews conducted with purposively selected practitioners. Findings revealed that while institutions actively use platforms such as Facebook, WhatsApp, Instagram, and Twitter for information dissemination, branding, and interaction, strategic evaluation and measurement of effectiveness remain weak. Respondents highlighted challenges such as inadequate digital infrastructure, poor analytic skills, and limited institutional investment in new communication tools. Nevertheless, evidence pointed to the capacity of social media to advance institutional visibility, strengthen identity, and foster deeper relationships with students, alumni, and the wider community when strategies are deliberately crafted and consistently evaluated. The study concludes that social media is not merely a supplement to traditional public relations but a vital arena for dialogue and institutional storytelling. It recommends structured policies, enhanced training for communication staff, and stronger commitment to evaluation frameworks in order to maximise the transformative potential of digital engagement in Nigerian tertiary institutions.